Chromosome-wide characterization of meiotic noncrossovers (gene conversions) in mouse hybrids. Issue 1 (23rd November 2020) - Gergelits, Vaclav; Parvanov, Emil; Simecek, Petr; Forejt, Jiri
Abstract: During meiosis, the recombination-initiating DNA double-strand breaks (DSBs) are repaired by crossovers or noncrossovers (gene conversions). While crossovers are easily detectable, noncrossover identification is hampered by the small size of their converted tracts and the necessity of sequence polymorphism. We report identification and characterization of a mouse chromosome-wide set of noncrossovers by next-generation sequencing of 10 mouse intersubspecific chromosome substitution strains. Based on 94 identified noncrossovers, we determined the mean length of a conversion tract to be 32 bp. The spatial chromosome-wide distribution of noncrossovers and crossovers significantly differed, although both sets overlapped the known hotspots of PRDM9-directed histone methylation and DNA DSBs, thus supporting their origin in the standard DSB repair pathway. A significant deficit of noncrossovers descending from asymmetric DSBs proved their proposed adverse effect on meiotic recombination and pointed to sister chromatids as an alternative template for their repair. The finding has implications for the molecular mechanism of hybrid sterility in mice from crosses between closely related Mus musculus musculus and Mus musculus domesticus subspecies.